Medical Students’ Attitudes towards and Beliefs about Dyslexia: A SingleCentre Survey Study - Laura R. Hennessy; Sebastian C. K. Shaw; John L. Anderson (International Journal of Social Sciences & Educational Studies, 2020)
Dyslexia impacts upon reading and writing, but not upon intelligence. Little research has explored dyslexia in medicine. An online questionnaire was emailed to all medical students within a single medical school, inviting them to participate. Results were analysed using descriptive statistics. Statistical significance was calculated for any differences between gender, age group, or year-group cohorts. 123 individuals responded. Most reported a good understanding of dyslexia, and feelings that their peers with it should be supported. However, a minority reported feelings of jealously, and dissatisfaction – feeling that students with dyslexia should not be supported, as this gives them an unfair advantage. In some, this seemed to stem from a belief that dyslexia were not real, or that their peers were “faking it”. “I think it is a poor excuse for students to be favoured advantageously and receive tremendous benefits. It is certainly not a medical problem.”